SISTEM PENYEBAR UNDANGAN DARING BERBASIS WEB MENGGUNAKAN QR CODE DI PT WIKA GEDUNG - Sodikin, Sodikin; Yatimollah, Yatimollah; Efendi, Yasin; Putri, Rahmawan (Jurnal Ilmiah Sistem Informasi, 2023)
The manual-based invitation spreader system that runs at PT Wika Gedung has not been able to send invitations to all guests and the right guests and makes the guests often missed. Methods that work like that are less effective. Meanwhile, what is needed by PT Wika Gedung is a system that can send invitations quickly and precisely to the intended invitation, and can monitor the attendance list of guests. Therefore, it is necessary to develop a QR Code-based online invitation spreader application to improve the effectiveness and accuracy of the data to be reported. The development method used is the Waterfall method, which is divided into 6 stages, namely interviews, analysis, design, implementation, testing, and maintenance. The phase aims to facilitate the division of modules and focus on the modules worked on. The result of this application is sending QR Code-based invitations and sending invitations to guests via e-mail addresses of each guest and can monitor the attendance of guests at certain events